Implementation of Group Counseling Services to Enhance Students' Self-Confidence Students at Integrated Islamic Junior High School Al Hijrah - Anggraini, Ayu; Lubis, Saiful Akhyar (Tarbiyah Wa Ta'lim: Jurnal Penelitian Pendidikan dan Pembelajaran, 2024)
Education is one of the efforts educators undertake to guide students towards maturity. However, this is often not accompanied by the necessary self-confidence among students, leading to negative impacts on the learning process. The objective of this research is to explore the implementation of group counseling services aimed at enhancing students' self-confidence at SMP IT Al-Hijrah. The research method employed is qualitative, utilizing data collection techniques such as interviews, observations, and documentation. The findings indicate that students' self-confidence increases after receiving group counseling services. Therefore, it can be concluded that group counseling services significantly enhance students' self-confidence in the learning process, particularly at SMP IT Al-Hijrah.